Acid-sensing ion channel 1a in the central nucleus of the amygdala regulates anxiety-like behaviors in a mouse model of acute pain - Shi, Pei; Zhang, Ming-Jun; Liu, An; Yang, Chen-Ling; Yue, Jia-Yin; Hu, Rui; Mao, Yu; Zhang, Zhi; Wang, Wei; Jin, Yan; Liang, Li-Shuang (Frontiers in Molecular Neuroscience, 2023)
Pain is commonly comorbid with anxiety; however, the neural and molecular mechanisms underlying the comorbid anxiety symptoms in pain (CASP) have not been fully elucidated. In this study, we explored the role of acid-sensing ion channel 1a (ASIC1a), located in GABAergic neurons from the central nucleus of the amygdala (GABACeA), in the regulation of CASP in an acute pain mouse model. We found that the mice displayed significant mechanical pain sensitization and anxiety-like behaviors one day post injection of complete Freud’s adjuvant (CFA1D). Electrophysiological recordings from acute brain slices showed that the activity of GABACeA neurons increased in the CFA1D mice compared with that in the saline mice. In addition, chemogenetic inhibition of GABACeA neurons relieved mechanical pain sensitization and anxiety-like behaviors in the CFA1D mice. Interestingly, through pharmacological inhibition and genetic knockdown of ASIC1a in the central nucleus amygdala, we found that downregulation of ASIC1a relieved the hypersensitization of mechanical stimuli and alleviated anxiety-related behaviors, accompanied with reversing the hyperactivity of GABACeA neurons in the CFA 1D mice. In conclusion, our results provide novel insights that ASIC1a in GABACeA neurons regulates anxiety-like behaviors in a mouse model of acute pain.